Development of a system to improve safety in switching of high voltage circuit breaker - Muhammad Atif, Bin Norzan Shah. (Universiti Malaysia Sarawak (UNIMAS), 2017)
The aim of this project is to create a safety system that develops a Pneumatic system to break High voltage switchgear (11KV to 33kV). This project has the grant scheme by OSAKA Gas Foundation in Cultural Exchanged Research (OGFIGE). It focuses on designing and constructing a switchgear breaker system that can do the switching process in substations without using any manpower and most of all, switching is done remotely by indisputable distances. By allowing service personnel to stand outside the arc-flash boundary at substations while assigned to do the switching, the remote switch operators reduce the need for a full-body arc flash hazard suit. The architecture and design of the remote switch system consist of 2.5 Horsepower Air Compressor, Electrical contacts, Contactor with ON and OFF contact, Circuit Breaker, Electro-pneumatic valve, Electro-pneumatic cylinder, Connecting wires, Ratchet Strap, and Pneumatic tubing and others. An optimum design of the remote switch is determined by its ability to break the actual Sarawak Energy selected Switchgears. Therefore, the size of the pneumatic cylinder is taken into consideration whether it is the optimum size to be installed onto the switchgear.